Case report: Anti-GAD65 antibody-associated autoimmune encephalitis following HPV vaccination - Li, Aonan; Hu, Ying; Li, Jialu; Chen, Xingui; Jiang, Yubao; Xie, Chengjuan (Frontiers in Neurology, 2022)
Human papillomavirus (HPV) infection is a sexually transmitted disease that may lead to cervical cancer. HPV vaccines have been implemented widely to prevent this. While generally few complications of vaccination are reported, there have been occasional reports of adverse reactions post-vaccination. The safety profile of the HPV vaccine is reassuring. However, since its introduction, several serious post-vaccination central nervous system complications have been reported; however, causality has not been established. Herein, we describe a 39-year-old woman who developed seizures and experienced a rapid decline in memory shortly after her first dose of the HPV vaccine. Cranial magnetic resonance imaging and cerebrospinal fluid analysis were performed, and the patient was diagnosed with anti-glutamic acid decarboxylase 65 (anti-GAD65) antibody-associated autoimmune encephalitis. She responded well to high-dose glucocorticoids. Four-month follow-up revealed full recovery and absence of recurrence. Since the HPV vaccine is administered worldwide, this case should raise clinicians' awareness regarding the possible CNS complications related to vaccinations, such as anti-GAD65 antibody-associated AE.